Integration of Services Onto Synchronous Digital Hierarchy Line Utilizing Wavelength Division Multiplexing - Ali @ Hasim, Norshamsuri (2005)
The access network growth has been a hot topic in recent telecommunication industries. Either in its applications, bandwidth offered, speed of data transferred or even the techniques used to achieve network growth. Many researchers have investigated this problem and come out with many solutions which are used in today's network in variety of applications and services. As the number of user and bandwidth grows, current network is incapable of managing the bandwidth demands. Another problem that limits this service is the availability of services in places far from the exchange office. This thesis proposes a new system with a new architecture to be implemented in the access network in order to solve this problem and provide flexibility in expansion the current network or system without intervening it. The proposal involves cascaded multiplexing technique which is based on Coarse Wavelength Division Multiplexing (CWDM). The cascaded multiplexing structure allows easy extension of the coverage span and CWDM provides asynchronous multiplexing at a considerably less cost than the DWDM version. Simulation and experimental work have been done in order to develop and test the system proposed to maximize the utilization of fiber, improve the performance, and increase the distance of transmission and the bandwidth support. This system is also studied in different formatting schemes and integration with amplifier. The proposed system can support the data bandwidth up to 2.5 Gbps with the maximum network coverage about 17 km in radii and optimal wavelength spacing of about 2 run (after consideration of wavelength shifting and laser spacing).